Students Challenges in Learning Public Speaking - Anggraini Eka Pratiwi; Riana Eka Budiastuti; Anjar Setiawan (UM Purwokerto Press, 2024)
This research aims to determine students' challenges in learning public speaking. This research method is descriptive quantitative. The subjects of this research are 5 male and 15 female students from University of Muhammadiyah Semarang in Kedung Mundu. The data collection technique uses questionnaires and interviews by giving a series of written and verbal questions or statements to respondents to then answer. The results show that there is easy learning when using Manuscript and Comunication in learning English. By applying the Manuscript method in learning public speaking, it shows an increase in self-confidence. Meanwhile, conversation can improve English pronunciation skills, habits, and increase English vocabulary which previously was one of the biggest challenges for students. Their tendency was to more easily improve Public Speaking by using the Manuscript model.